Exploring the link between acute symptom changes and repetitive head impacts in boxing sparring - Le Flao, E.; Siegmund, G. P.; Lenetsky, S.; Borotkanics, R. (Journal of Science and Medicine in Sport, 2026)
Objectives The acute dose-response relationship between head impact exposure and the development of concussion remains elusive. Previous research has suggested that individual-specific approaches and the cumulative effects of head impacts should be investigated. This study aimed to monitor acute changes in concussion-related symptoms resulting from boxing sparring, and assess how they relate to head impact exposure.